Identification of the running status of membrane walls in an opposed fired model boiler under varying heating loads. (5th June 2020) - Fu, Jiapeng; Liu, Zhuhan; Wei, Lin; Lin, Leteng; Li, Na; Zhou, Qulan; Ma, Chunyuan
Highlights: Membrane wall temperature, heat flux, strain and stress distributions were mapped. An area with overlapped high temperature and stress is identified on side walls. Wall temperature and fix constraints determined strain and stress distributions. Average values of strain and stress kept almost stable under varying heat loads. Abstract: To understand the running status of membrane walls in an opposite firing boiler, a scale-down model furnace was established, and the temperature, heat flux, strain and stress distributions are investigated under four heating loads. Results show that the average membrane wall temperature and heat flux present a continuous increase from 42 °C and 16 W/m 2 to 96 °C and 50 W/m 2, respectively, with the heating load increase from 25% to full load. The average strain and stress also rise from 88.7 µm and 0.094 MPa to 152.5 µm and 0.148 MPa when the heating load increases from 25% to 50%, but then they keep stable when further increasing the heating load. General distribution patterns of each tested parameter are found relatively similar under varying heating loads. High strain and stress distributions are always detected at the middle left zone of side walls and the middle of the rear wall, where wall temperatures are measured high. External fixed constraints and high-temperature thermal strain is found jointly affecting the strain and stress distribution of the membrane wall. A simplified mechanism of how the strain and stress on boiler membrane walls evolve is proposed after comprehensive discussion of the measurement results.